2018
DOI: 10.1039/c8nr07202g
|View full text |Cite
|
Sign up to set email alerts
|

The equilibrium structure of self-assembled protein nano-cages

Abstract: Understanding how highly symmetric, robust, monodisperse protein cages self-assemble can have major applications in various areas of bio-nanotechnology, such as drug delivery, biomedical imaging and gene therapy. We develop a model to investigate the assembly of protein subunits into the structures with different size and symmetry. Using Monte Carlo simulation, we obtain the global minimum energy structures. Our results suggest that the physical properties of building blocks including the spontaneous curvature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 45 publications
5
43
0
Order By: Relevance
“…Notice that the particular geometrical configuration of the subunit at the rim of the assembly favors defect nucleation rather than bulk defect mobility, whatever the physical parameters. This qualitative analysis is consistent with the recent work by Panahandeh et al who compared directly the phase diagram of irreversible and relaxed self-assembly [30]. They found that for most of the phase diagram, the structures are very similar.…”
Section: Discussionsupporting
confidence: 92%
“…Notice that the particular geometrical configuration of the subunit at the rim of the assembly favors defect nucleation rather than bulk defect mobility, whatever the physical parameters. This qualitative analysis is consistent with the recent work by Panahandeh et al who compared directly the phase diagram of irreversible and relaxed self-assembly [30]. They found that for most of the phase diagram, the structures are very similar.…”
Section: Discussionsupporting
confidence: 92%
“…[ 38 ] In their model, growth is guided by internal elastic stresses born out of mechanical properties of the subunits and geometric frustration. In a subsequent paper, [ 39 ] they found striking similarities between the minimum free energy structure diagram and the diagram obtained via irreversible growth. These new simulations recapitulate the formation of high‐symmetry shells as well as of lower symmetry ones.…”
Section: Resultsmentioning
confidence: 83%
“…The fact that most spherical viruses adopt structures with icosahedral symmetry reveals the important role of elasticity in the energetics of viral shells [44,53,54]. Nevertheless, it has remained a mystery how an error-free shell formed out of 90 dimers or 60 trimers grows with perfect icosahedral symmetry under many different in vitro assembly conditions.…”
Section: Empty Capsidsmentioning
confidence: 99%